Akselerasi Waktu Pelaporan Operasi Irigasi Menggunakan Perangkat Lunak Berbasis Web Sistem Manajemen Operasi dan Pemeliharaan Irigasi (SMOPI) - Sofiyuddin, Hanhan Ahmad; Rahmandani, Dadan (Balai Teknik Irigasi, 2019)
More efficient irrigation management is needed in the face of limited water availability and the increasing water requirements for other than agricultural sectors. This can be done by improving the accuracy of irrigation water through the optimizing of irrigation operation intervals. One effort which can be done is minimizing the time needed to report irrigation operation activities. using web-based application Irrigation Operations Management System (SMOPI). Research is conducted to identify the minimum time required for the reporting of irrigation operations, either manually or using SMOPI. The research was conducted as a case study in the Bondoyudo irrigation area by means of the collection of data through discussions and questionnaires as well as analysis of the time needed to report irrigation operation activities using the Critical Path Method. The result showed that the manual irrigation operations take 43 hours at the crop planning stage, 41 hours at the water delivery management, and 45 hours at the result recapitulation stage. The requirement of about 5 days at the implementation stage indicates that the operating interval of existing irrigation every 10 days is quite feasible. SMOPI is able to accelerate so that the operation time at the crop planning, water delivery management, and result recapitulation stage are 24.5 hours, 14 hours, and 31,5 hours. This indicates that SMOPI can be used to help shorten the interval of irrigation operations to support irrigation modernization.